An IRF-3-, IRF-5-, and IRF-7-Independent Pathway of Dengue Viral Resistance Utilizes IRF-1 to Stimulate Type I and II Interferon Responses - Aaron F. Carlin; Emily M. Plummer; Edward A. Vizcarra; Nicholas Sheets; Yunichel Joo; William Tang; Jeremy Day; Jay Greenbaum; Christopher K. Glass; Michael S. Diamond; Sujan Shresta (Cell Reports, 2017)
Summary: Interferon-regulatory factors (IRFs) are a family of transcription factors (TFs) that translate viral recognition into antiviral responses, including type I interferon (IFN) production. Dengue virus (DENV) and other clinically important flaviviruses are suppressed by type I IFN. While mice lacking the type I IFN receptor (Ifnar1−/−) succumb to DENV infection, we found that mice deficient in three transcription factors controlling type I IFN production (Irf3−/− Irf5−/− Irf7−/− triple knockout [TKO]) survive DENV challenge. DENV infection of TKO mice resulted in minimal type I IFN production but a robust type II IFN (IFN-γ) response. Using loss-of-function approaches for various molecules, we demonstrate that the IRF-3-, IRF-5-, IRF-7-independent pathway predominantly utilizes IFN-γ and, to a lesser degree, type I IFNs. This pathway signals via IRF-1 to stimulate interleukin-12 (IL-12) production and IFN-γ response. These results reveal a key antiviral role for IRF-1 by activating both type I and II IFN responses during DENV infection. : Carlin et al. identify a non-canonical IRF-3-, IRF-5-, and IRF-7-independent antiviral defense mechanism that mediates protection against severe dengue disease. This alternative pathway utilizes IRF-1, predominantly via IL-12/IFN-γ, enabling survival in the context of reduced type I IFN responses. Keywords: dengue, interferon, IFNs, IRF-1, IRFs, mouse models, macrophages, IL-12, innate immunity, flavivirus